2015
DOI: 10.1038/nrmicro3417
|View full text |Cite
|
Sign up to set email alerts
|

Marine microbial community dynamics and their ecological interpretation

Abstract: Recent advances in studying the dynamics of marine microbial communities have shown that the composition of these communities follows predictable patterns and involves complex network interactions, which shed light on the underlying processes regulating these globally important organisms. Such 'holistic' (or organism- and system-based) studies of these communities complement popular reductionist, often culture-based, approaches for understanding organism function one gene or protein at a time. In this Review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
575
5
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(616 citation statements)
references
References 135 publications
26
575
5
10
Order By: Relevance
“…Time scale appears to be an important determinant of organismal associations. We previously reported that members of the SAR11 cluster were correlated on a daily time scale but not monthly (Fuhrman and Steele, 2008;Steele et al, 2011;Needham et al, 2013;Fuhrman et al, 2015), reflecting patterns of temporal variability in network structure seen in other systems (Alarcón et al, 2008). A common feature of networks is the presence of modules, that is, highly interconnected groups of nodes (Newman, 2006;Olesen et al, 2007;Ings et al, 2009) and microbial networks are no exception Chow et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time scale appears to be an important determinant of organismal associations. We previously reported that members of the SAR11 cluster were correlated on a daily time scale but not monthly (Fuhrman and Steele, 2008;Steele et al, 2011;Needham et al, 2013;Fuhrman et al, 2015), reflecting patterns of temporal variability in network structure seen in other systems (Alarcón et al, 2008). A common feature of networks is the presence of modules, that is, highly interconnected groups of nodes (Newman, 2006;Olesen et al, 2007;Ings et al, 2009) and microbial networks are no exception Chow et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial communities throughout the water column show long-term, seasonal and short-term dynamics that relate to various biological, chemical and physical environmental parameters (Gilbert et al, 2012;Giovannoni and Vergin, 2012;Chow et al, 2013;Hatosy et al, 2013;Needham et al, 2013;Cram et al, 2014a;Fuhrman et al, 2015). Microbial interactions have been observed experimentally (Jurgens et al, 1999;Miller and Bassler, 2001;Jürgens and Matz, 2002;Bonilla-Findji et al, 2009) through physical attachment ) and inferred through genomic and physiological information (for example, Bothe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…So far, studies of marine mycoplankton diversity have been largely based on samples collected from one-off sampling campaigns that have provided important and insightful 'snap shots' of diversity, but with limited temporal resolution (Bass et al, 2007;Gao et al, 2010;Richards et al, 2012;Manohar and Raghukumar, 2013;. Time series assessments of other plankton groups have proven invaluable in developing our understanding of their biology and ecology (Karl and Church, 2014;Fuhrman et al, 2015). Spatially defined and reoccurring assessments of plankton diversity and abundance that are aligned with co-occurring environmental variables (temperature, nutrients and so on) have been used to identify the key controlling environmental drivers that influence planktonic organisms, and to form the basis of establishing the underpinning principles of their ecologies and ecosystem functional roles.…”
Section: Introductionmentioning
confidence: 99%
“…Los océanos son los ambientes de mayor extensión en el planeta y los microorganismos son la parte dominante tanto en biomasa como en actividad metabólica, por lo que el estudio de la composición y dinámica de las poblaciones microbianas marinas es muy importante (Fuhrman et al 2015). En el océano, los microorganismos son los que capturan y traducen la energía solar, catalizan las transformaciones biogeoquímicas clave de los nutrientes y elementos traza que soportan la productividad oceánica, participan en la regulación de los gases de efecto invernadero y representan una gran reserva de variabilidad genética (Karl 2007, Karl y Church 2014.…”
Section: Marine Microbial Communitiesunclassified
“…The study of the composition and dynamics of marine microbial communities is therefore of the utmost importance (Fuhrman et al 2015). In oceans, microorganisms capture and convert solar energy, catalyze key biogeochemical transformations of nutrients and trace elements that support productivity, participate in the regulation of greenhouse gases, and represent a vast reservoir of genetic diversity (Karl 2007, Karl andChurch 2014).…”
Section: Introductionmentioning
confidence: 99%